2018
DOI: 10.1080/1359432x.2018.1515200
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Triad and competitive psychological climate at work: A model of reciprocal relationships in dependence of age and organization change

Abstract: Integrating an interactionist model of personality development, the cumulative continuity model of personality development, and selection-evocation-manipulation theory, the present study analysed reciprocal relations of the Dark Triad common core and its sub-traits of narcissism, psychopathy, and Machiavellianism with competitive psychological climate. Moreover, within a large (N = 1,185) and longitudinal sample of employees from Germany, latent cross-lagged panel analyses were applied to analyse the moderatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 88 publications
2
11
0
4
Order By: Relevance
“…Similar results have been found for a competitive psychological work climate (Spurk and Hirschi 2018). Spurk and Hirschi (2018) even found that individuals DT tendencies increase when working under what they perceive as competitive conditions.…”
Section: Theoretical Implicationssupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results have been found for a competitive psychological work climate (Spurk and Hirschi 2018). Spurk and Hirschi (2018) even found that individuals DT tendencies increase when working under what they perceive as competitive conditions.…”
Section: Theoretical Implicationssupporting
confidence: 84%
“…Contrarily, an individual-centered climate encourages employees to manipulate, cheat, and violate norms of the organization (Suar and Khuntia 2004). Similar results have been found for a competitive psychological work climate (Spurk and Hirschi 2018). Spurk and Hirschi (2018) even found that individuals DT tendencies increase when working under what they perceive as competitive conditions.…”
Section: Theoretical Implicationssupporting
confidence: 69%
“…It is therefore very possible that the differences in the "dark triad" structure were driven by other factors beyond age. Nevertheless, this study, as well as a related study by Spurk & Hirschi (2018), indicates that the assumption that socially aversive personality measures are invariant or that manifestations of these traits are the same across the age range might be false, which could result in misleading interpretations of age trends in socially aversive personality traits.…”
Section: Age-associated Mean Trends In Socially Aversive Personalitymentioning
confidence: 58%
“…For instance, in two papers Kirchler et al (2018) and Kirchler et al (2020) report higher levels of competitiveness among finance professionals compared to students, academics, and the general population, but lower levels compared to professional athletes. Perceived competitiveness has been shown to be related to higher levels of psychopathy (Jonason et al, 2015;Spurk and Hirschi, 2018). The trait of psychopathy is particularly relevant for financial decision-making, since it explains misbehavior in taking risk on behalf of others (Jones, 2014) and gambling with money of somebody else (Jones, 2013).…”
Section: Personality Traitsmentioning
confidence: 99%